EFEKTIVITAS SOSIALISASI PENDIDIKAN POLITIK BERBASIS AUDIO VISUAL TERHADAP PERUBAHAN PENGETAHUAN POLITIK PEMILIH PEMULA - Sri Wulan Ahdarianti.A Wulan; Ofi Hidayat (Social and Political Sciences Faculty, Widya Gama Mahakam Samarinda University, 2023)
Indonesia in 2024 will face a grand democratic party that will make big decisions for Indonesia's future. Along with this grand performance, another big potential that is highlighted by many parties is the number of first-time voters, which is estimated to reach 60%, dominating voters in Indonesia. This great potential is of concern to many parties to make efforts to provide political education through various media. The purpose of this study seeks to examine the use of political education media and its effectiveness in increasing the political knowledge of first-time voters. This study uses the Quasi Experiment research method, precisely The Non Equivalent Control Group, with testing media using the pre-test and post-test. The study found that there was a significant effect of the use of audio-visual media on increasing the knowledge of novice voters before and after being given audio-visual-based political education. Other findings that try to compare the effectiveness of the use of audio visual with classical media found no significant difference between the two. Thus the use of audio-visual media to increase political knowledge is specifically influential but when compared to classical media it is still the same.